Pseudo-Intellectualism and Artificial Intelligence: A Phenomenological Study of Student Intellectuality in the Digital Age - Awaludin Hamzah (Institut Agama Islam Persis Bandung, 2024)
The integration of artificial intelligence (AI) in education has triggered an epistemological crisis that threatens the intellectual character of students. This qualitative study aims to explore the dynamics of student digital literacy in the AI era through a phenomenological approach. The results reveal four crucial phenomena: erosion of articulation independence, dependence on probabilistic algorithms, decreased mental endurance in research, and the emergence of an illusion of competence. The findings show that easy access to AI often replaces the process of cognitive struggle with